تقويم حالة تسمم جماعي بالميتانول في مشفى الباسل بطرطوس من الوجهة الطبية الشرعية - سليمان, جابر (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 43 حالة تسمم حاد بالكحول الميتيلي تم قبولها في مشفى الباسل بطرطوس خلال شهر حزيران عام 2003. كان من بين المرضى أنثى واحدة مقابل 42 من الذكور. تراوحت الأعمار بين 16 سنة وحتى 80 سنة مع ذروة حدوث في العقد الرابع (14 حالة أي 32.5% ). اعتمد التشخيص على قصة تناول الكحول مع وجود الأعراض السريرية، وخاصةً تشوش الرؤية. بلغ عدد الوفيات8 ، ( أي 19 % )، وأهم الاختلاطات: ضعف رؤية مع وذمة حليمة العصب البصري (حالتان)، وعمى كامل ( حالتان ) بينما انتهت 31 حالة بالشفاء التام ( 71 % ). شملت الثغرات الأساسية عدم الاعتماد على معايرة الكحول الميتيلي ومستقلباته في الدم لتأكيد التشخيص، بالإضافة إلى عدم إجراء الخبرة الطبية الشرعية الأكاديمية في الوقت المناسب. This study includes 43 cases of acute poisoning with methanol, which were admitted to Al Bassel Hospital in Tartous in June 2003. Only one of them was a female. Their age ranged between 16 - 80 years. The peak incidence was between 30 - 40 years. The diagnosis was based on the history alcohol intake, signs and clinical symptoms, and especially blurred vision. The incidence of death was 19 % (8 patients). The other complications include papilloedema and reduced vision in 2 patients, and 2 patients were blinded. 31 patients have hade complete recovery (71 %). The main defects were that blood determination of methanol and its metabolites were not available and forensic medical experience was not properly done.